2009
DOI: 10.1080/08820130902745146
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Gene Polymorphism and Susceptibility to Ischemic Stroke

Abstract: Cytokines gene polymorphisms have been implicated in susceptibility to ischemic stroke. This study aims to determine the influence of the polymorphism within the intron 2 of the interleukin- 1 receptor antagonist (IL-1Ra) gene on the susceptibility to stroke. A variable number of tandem repeats (VNTR) in intron 2 of the IL-1Ra gene was analyzed in 148 patients with stroke and 161 healthy volunteers from the same area. The carriage rate of allele 2 of IL-1Ra gene, low producer, was significantly higher in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This hypothesis is in line with other studies which reported not only a close association of IL1RN*2 allele with severe clinical outcome in chronic inflammatory diseases [38,39], but also supported a role of this polymorphic allele in determining the genetic susceptibility to progressive brain changes that might occur over time during the illness. Supporting this speculation are in vitro studies demonstrating that high IL-1β concentrations can decrease neuronal survival and may promote the neurodegeneration observed in schizophrenia [5,30,40].…”
Section: Discussionsupporting
confidence: 81%
“…This hypothesis is in line with other studies which reported not only a close association of IL1RN*2 allele with severe clinical outcome in chronic inflammatory diseases [38,39], but also supported a role of this polymorphic allele in determining the genetic susceptibility to progressive brain changes that might occur over time during the illness. Supporting this speculation are in vitro studies demonstrating that high IL-1β concentrations can decrease neuronal survival and may promote the neurodegeneration observed in schizophrenia [5,30,40].…”
Section: Discussionsupporting
confidence: 81%
“…Four studies were hospital-based case-controls studies (Chamorro et al, 2005;Dziedzic et al, 2005;Flex et al, 2004;Um et al, 2003a), thirteen studies were population-based case-control studies, and one study (Worrall et al, 2007) did not report the source of controls. All of the studies were in goodness-in-fitness of HWE except for three studies (Lee et al, 2010;Li et al, 2010;Rezaii et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In total, twenty case-control studies in seventeen articles (Balding et al, 2004;Banerjee et al, 2008;Chamorro et al, 2005;Dziedzic et al, 2005;Flex et al, 2004;Iacoviello et al, 2005;Lai et al, 2006;Lalouschek et al, 2006;Lee et al, 2010;Li et al, 2010;Rezaii et al, 2009;Rubattu et al, 2005;Seripa et al, 2003;Tong et al, 2010;Um et al, 2003a;Worrall et al, 2007;Zee et al, 2008) were included in this meta-analysis. Of these studies, five studies (Lai et al, 2006;Lee et al, 2004;Li et al, 2010;Tong et al, 2010;Um et al, 2003a) were for Asians, one study (Worrall et al, 2007) was for American Africans, and the other studies were for Caucasians.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the neuronal NLRP1 inflammasome (which is involved in the processing and release of IL-1 through the activation of caspase-1) improves outcome after stroke, traumatic or spinal cord injury [19,20,21]. Further support for a role for IL-1 in stroke comes from the observations that IL-1 or IL-1Ra gene polymorphisms are associated with altered susceptibility to stroke, carotid atherosclerosis and intracranial haemorrhage in humans [22,23,24,25,26,27]. …”
Section: Il-1 and Acute Brain Injurymentioning
confidence: 99%